Postpartum Serum Non-Esterified Fatty Acids, Milk Yield, Feed Intake and Plasma Natural Antibodies in Cows with Subclinical Mastitis - Mayasari, Novi Mayasari; Wulansari, Asri; Ismiraj, Muhammad Rifqi; Firmansyah, Indra (Jurnal Sain Veteriner, 2025)
Somatic cell count (SCC) is commonly used as an indicator of subclinical mastitis, yet its association with postpartum performance, non-esterified fatty acid (NEFA) concentration, and immune status remains unclear. This study evaluated 18 Holstein Friesian cows grouped by milk SCC: low (<160,000 cells/ml), moderate (160,000–400,000 cells/ml), or high (>400,000 cells/ml). Daily milk production, feed intake, plasma NEFA levels, and natural antibodies (IgG and IgM) against keyhole limpet hemocyanin (KLH) were measured. ANOVA was used to detect differences among groups. Despite consistent feeding regimens and standardized sampling, cows with high SCC (4.79) tended to exhibit lower IgG titers than those with low (6.16) and moderate (6.42) SCC, suggesting reduced immune function under higher SCC levels. However, milk yield, feed intake, IgM titers, and postpartum NEFA levels showed no significant differences among the three groups. These findings indicate that elevated SCC may impair systemic IgG antibody responses but exerts limited effects on production and metabolic parameters. In conclusion, while SCC appears to influence immune status, its relationship with NEFA concentrations, milk production, and feed intake is less pronounced under these experimental conditions.